2020
DOI: 10.1186/s13071-020-04073-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intestinal parasites on microbiota and cobalamin gene sequences: a pilot study

Abstract: Background: Approximately 30% of children worldwide are infected with gastrointestinal parasites. Depending on the species, parasites can disrupt intestinal bacterial microbiota affecting essential vitamin biosynthesis.Methods: Stool samples were collected from 37 asymptomatic children from a previous cross-sectional Argentinian study. A multi-parallel real-time quantitative PCR was implemented for Ascaris lumbricoides, Ancylostoma duodenale, Necator americanus, Strongyloides stercoralis, Trichuris trichiura, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 63 publications
4
24
0
Order By: Relevance
“…We reasoned that parasite-induced perturbations in the microbiome could also be an important factor influencing gastrointestinal symptoms. Our results, in combination with similar results from recent smaller-scale mouse and human experiments ( 62 , 63 ), raise the possibility that the shift in microbiome composition during Giardia infection—marked by a reduction in Gammaproteobacteria and an increase in Prevotella —may explain, at least in part, the apparent protective effect of Giardia against diarrhea in some age/site cohorts ( 30 , 34 , 56 ).…”
Section: Discussionsupporting
confidence: 87%
“…We reasoned that parasite-induced perturbations in the microbiome could also be an important factor influencing gastrointestinal symptoms. Our results, in combination with similar results from recent smaller-scale mouse and human experiments ( 62 , 63 ), raise the possibility that the shift in microbiome composition during Giardia infection—marked by a reduction in Gammaproteobacteria and an increase in Prevotella —may explain, at least in part, the apparent protective effect of Giardia against diarrhea in some age/site cohorts ( 30 , 34 , 56 ).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, children infected with Giardia present a shift from enterotype I to enterotype II, characterized by an increase of Prevotella and a decrease of Bacteroides ( Toro-Londono et al, 2019 ). Significant increases in Prevotella were also observed in Argentinian children infected with Giardia compared to uninfected individuals ( Mejia et al, 2020 ). Interestingly, Giardia infection was associated with a decreased abundance of microbiome Vitamin B12 (cobalamin) biosynthesis genes (CbiM), which has been associated with impaired growth and development in children ( Mejia et al, 2020 ).…”
Section: Alterations To the Microbiota During Giardia mentioning
confidence: 99%
“…During the acute phase of infection, Giardia actively interacts with the intestinal surface, causing epithelial damage, mucus layer disruptions, and gut microbiota dysbiosis [4,7,26,27,42]. These effects may occur at the site of infection and beyond, and result at least in part from the actions of Giardia excretory and secretory products and the host immune response ( [28,35], Gruettner p. 221 in [31]).…”
Section: Production Of Diseasementioning
confidence: 99%
“…These effects may occur at the site of infection and beyond, and result at least in part from the actions of Giardia excretory and secretory products and the host immune response ( [28,35], Gruettner p. 221 in [31]). Giardia cysteine proteases appear to play a critical role in the interactions between host intestinal epithelial cells and the parasite (Peirasmaki p. 89 in [31]; Gruettner p. 221 in [31]), as they do in the microbiota dysbiosis it induces [27]. Elegant studies A.G. Buret et al: Parasite 2020, 27, 49 using murine model systems confirmed that infection with Giardia disrupts intestinal microbiota and pave the way towards more research into microbiome-Giardia interactions (Starcevich p. 83 in [31]).…”
Section: Production Of Diseasementioning
confidence: 99%